Obstetric anal sphincter injuries before and after the introduction of the Episcissors-60: A multi-centre time series analysis. (October 2019) - Ayuk, Paul; Farnworth, Allison; Rees, Jon; Khunda, Aethele; Edmundson, Dawn; Raheja, Vinita; Ullal, Aarti; Ravimohan, Velauthapillai; Lu, Ena; Robson, S.C.
Abstract: Objective: To investigate the impact of the Episcissors-60 on obstetric anal sphincter injury (OASI) rates. Study design: Observational multi-centre time series analysis at four maternity units in the North-East of England. The main outcome measures were obstetric anal sphincter injury rates and delivery blood loss. Results: Data were analysed for women who had a vaginal birth of a singleton pregnancy before (11, 192) and after (8064) the introduction of the Episcissors-60. There were 2115 episiotomies before and 1498 after the introduction of the Episcissors-60, of which 1311 (87.5%) were undertaken with the Episcissors-60, 114 (7.6%) with other scissors and the scissors used were not stated in 73 (4.8%) women. There was no significant association between the introduction of Episcissors-60 and the performance of an episiotomy (χ 2 = 0.006, p = 0.94). Episiotomy was associated with a significant reduction in OASI rates (1.9% Vs 2.8%, odds ratio = 0.67 [0.51 – 0.86]; p = 0.001). There was no significant association between the introduction of the Episcissors-60 and the occurrence of OASIs in all women (χ 2 = 0.6, p = 0.46) or in women who had an episiotomy (χ 2 = 0.20, p = 0.71). In women who had an episiotomy, the mean estimated delivery blood loss was 550.3 ± 8.2 ml before and 598.8 ± 10.9 ml after the introduction of the Episcissors-60 ( p < 0.001). Conclusion: Introduction of the Episcissors-60 was not associated with a change in OASI or episiotomy rates but may be associated with a small increase in delivery blood loss.